Islamophobia, Victimisation and the Veil - Zempi, I. author. aut Link
VIII, 109 p.
Keywords: This book examines the experiences of veiled Muslim women as victims of Islamophobia, and the impact of this victimisation upon women, their families and wider Muslim communities. It proposes a more effective approach to engaging with these victims; one which recognises their multiple vulnerabilities and their distinct cultural and religious needs.